A Moderated Mediation Model of Self-Concept Clarity, Transformational Leadership, Perceived Work Meaningfulness, and Work Motivation - Oh, Sunyoung; Roh, Sang-Choong (Frontiers in Psychology, 2019)
The purpose of this study was to investigate the role of self-concept clarity in predicting employees’ perceived work meaningfulness. We proposed a moderated mediation model in which perceived work meaningfulness could mediate the relationship between self-concept clarity and work motivation, and transformation leadership could moderate this mediating relationship. We tested our hypotheses using data collected from 488 employees in various companies. Results showed that individual differences in self-concept clarity were positively related to perceived work meaningfulness, and perceived work meaningfulness mediated the relationship between self-concept clarity and work motivation. Furthermore, the strength of indirect relationship between self-concept clarity and work motivation via perceptions of work meaningfulness was stronger when transformational leadership was low than when it was high. Implications of our findings along with limitations of this study and directions for future research are also discussed.